2023
DOI: 10.3389/feart.2022.1097551
|View full text |Cite
|
Sign up to set email alerts
|

Study on deformation control of overlying strata in short-wall coordinated filling mining of thick coal seam under aquifer

Abstract: The mining of coal resources and the protection of water resources are often in opposition, and this contradiction is more prominent in the mining of thick coal seams due to the difficulty of controlling the overburden deformation. Based on the mining conditions of thick coal seam under the main aquifer of a coal mine in the water shortage area of Northwest China, this paper puts forward the short-wall coordinated filling mining (SCFM) of thick coal seam. The stress analysis of the overall structure consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Harmonic extraction was initially used to control surface movement and deformation in three-underground mining 6 , 7 , which involves using multiple adjacent coal mining faces to maintain a particular relationship in time and space to offset uneven surface subsidence and deformation. Research and production practice has shown that coordinated mining can effectively reduce the degree of surface deformation and unevenness 8 , 9 . Drawing inspiration from the concept of harmonic extraction, this article takes the upward mining problem of the No.1 coal seam in the fifth panel of Zaoquan Coal Mine as the background and comprehensively adopts theoretical analysis, similarity simulation, and numerical calculation research methods to determine the relatively reasonable layout positions of the No.2 coal seam, No.6 and 7 coal seam working faces, which can provide reference for the mining layout design of similar working conditions in mines.…”
Section: Introductionmentioning
confidence: 99%
“…Harmonic extraction was initially used to control surface movement and deformation in three-underground mining 6 , 7 , which involves using multiple adjacent coal mining faces to maintain a particular relationship in time and space to offset uneven surface subsidence and deformation. Research and production practice has shown that coordinated mining can effectively reduce the degree of surface deformation and unevenness 8 , 9 . Drawing inspiration from the concept of harmonic extraction, this article takes the upward mining problem of the No.1 coal seam in the fifth panel of Zaoquan Coal Mine as the background and comprehensively adopts theoretical analysis, similarity simulation, and numerical calculation research methods to determine the relatively reasonable layout positions of the No.2 coal seam, No.6 and 7 coal seam working faces, which can provide reference for the mining layout design of similar working conditions in mines.…”
Section: Introductionmentioning
confidence: 99%